1984
DOI: 10.1159/000275698
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Multiple Supraglottic Squamous Cell Papillary Carcinoma in an Adult

Abstract: Invasive papillary squamous cell carcinoma of the supraglottic larynx is described in an adult male. The clinicopathological appearance was that of a multiple growth which displayed various gradients of neoplastic changes: in situ, microinvasion, frank invasion of cartilage and cervical node metastases. No previous history of radiotherapy was elicited. The growth was excised by supraglottic laryngectomy and neck dissection. Typical metastatic papillary formations were observed in lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The diagnosis of PSCC was established on the basis of histological features. In 8 cases (5 cases in Cardesa et al, 5 1 case in Ereño et al, 13 1 case in Shanon et al, 14 and 1 case in Judd et al 16 ), papillary carcinoma with microinvasion or infiltration of the submucosal tissue was observed. In the majority of patients, cytopathic effect was not observed in the biopsy specimens.…”
Section: Diagnosismentioning
confidence: 93%
See 2 more Smart Citations
“…The diagnosis of PSCC was established on the basis of histological features. In 8 cases (5 cases in Cardesa et al, 5 1 case in Ereño et al, 13 1 case in Shanon et al, 14 and 1 case in Judd et al 16 ), papillary carcinoma with microinvasion or infiltration of the submucosal tissue was observed. In the majority of patients, cytopathic effect was not observed in the biopsy specimens.…”
Section: Diagnosismentioning
confidence: 93%
“…8 The analysis of age shows that the majority of patients were on average more than 50 years of age. 3,7,8 The most common site involved was the larynx (3 cases in Cardesa et al, 5 17 cases in Suarez et al, 8 1 case in Ereño et al, 13 and 1 case in Shanon et al 14 ), followed by the alveolar ridge (20 cases in Ishiyama et al 3 ). The other sites affected were buccal mucosa (13 cases in Ishiyama et al 3 and 2 cases in Takeda et al 15 ), sinonasal tract (11 cases in Suarez et al 8 and 1 case in Judd et al 16 ), nasopharynx, 5 and oropharynx.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor is an entity, with few cases published in the literature, which is mainly located in the supraglotic region [4,5]. Like the rest of HNSCC, a relationship between PSCC with HPV infection has been published recently [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the rst mentions of a papillary tumour in this region was made in the sixties by Parkhill, 3 who described a papillary tumour in the palatine tonsil. More recently, Shano et al 4 reported an invasive and metastasizing PSCC of the supraglottic larynx.…”
Section: Introductionmentioning
confidence: 99%